MODEL PENDAMPINGAN DALAM MEWUJUDKAN JIWA KEWIRAUSAHAAN BAGI ANAK JALANAN DI KOTA PALEMBANG - Dedi Rianto Rahadi (Jurnal Universitas Paramadina, 2014)
AbstractEntrepreneurial spirit can have the character of street children through  education, hard work and comprehensive knowledge. The general objective  of the research is to produce a model entrepreneur community among street children and realize the nature and behavior of self to not be  a burden to others. The study design was a multiple case study.  Methods of data collection using a combination of approaches (triangulat  which include: surveys, observation, field study, FGD (focus group  discussion), PRA (Participatory rural appraisals) and action research.  Samples numbered 33 street children in the city of Palembang, results  showed some children street in the city of Palembang born of the economic  downturn the bottom layer of society. they become street  children due to the low socio-economic conditions of the family and his  efforts to use the money to support their families and personal needs such  as playing online games at Internet cafes. Activities undertaken by  street children is singing on the bus, begging, hawkers (selling  newspapers, food and soft drinks). Conclusions Entrepreneur modeling  studies can be done through family empowerment approaches and models  of mentoring, especially in terms of economy, education and  religion. Through family involvement can accelerate the growth of the  entrepreneurial spirit for street children